A clinical decision-making algorithm for penicillin allergy. (17th November 2017) - Soria, Angèle; Autegarden, Elodie; Amsler, Emmanuelle; Gaouar, Hafida; Vial, Amandine; Francès, Camille; Autegarden, Jean-Eric
Abstract: Background: About 10% of subjects report suspected penicillin allergy, but 85–90% of these patients are not truly allergic and could safely receive beta-lactam antibiotics Objective: To design and validate a clinical decision-making algorithm, based on anamnesis (chronology, severity, and duration of the suspected allergic reactions) and reaching a 100% sensitivity and negative predictive value, to assess allergy risk related to a penicillin prescription in general practise. Study design and methods: All patients were included prospectively and explorated based on ENDA/EAACI recommendations. Results of penicillin allergy work-up (gold standard) were compared with results of the algorithm. Results: Allergological work-up diagnosed penicillin hypersensitivity in 41/259 patients (15.8%) [95% CI: 11.5–20.3]. Three of these patients were diagnosed as having immediate-type hypersensitivity to penicillin, but had been misdiagnosed as low risk patients using the clinical algorithm. Thus, the sensitivity and negative predictive value of the algorithm were 92.7% [95% CI: 80.1–98.5] and 96.3% [95% CI: 89.6–99.2], respectively, and the probability that a patient with true penicillin allergy had been misclassified was 3.7% [95% CI: 0.8–10.4]. Conclusions: Although the risk of misclassification is low, we cannot recommend the use of this algorithm in general practice. However, the algorithm can be useful in emergency situations in hospital settings. Key messages: True penicillin allergy is considerably lower than alleged penicillin allergy (15.8%; 41 of the 259 patients with suspected penicillin allergy). A clinical algorithm based on the patient's clinical history of the supposed allergic event to penicillin misclassified 3/41 (3.7%) truly allergic patients.